2017
DOI: 10.1002/jum.14501
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial and Intracranial Ultrasonographic Findings in Posterior Circulation Infarction

Abstract: Vertebral artery hypoplasia and a low velocity in the intracranial vertebrobasilar system on US might change the treatment of patients with posterior circulation infarction for primary and secondary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
(84 reference statements)
1
20
0
Order By: Relevance
“…Chi et al (13) used 100 mL/min as a cut-off value to show that 72.5% of stroke patients had normal NVAFV. This finding is close to our result of 80.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Chi et al (13) used 100 mL/min as a cut-off value to show that 72.5% of stroke patients had normal NVAFV. This finding is close to our result of 80.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoperfusion determined using large-vessel quantitative magnetic resonance angiography is closely associated with the risk of stroke in patients with symptomatic atherosclerotic vertebral basilar artery occlusive disease [11]. TCD demonstrated a decreasing trend of blood ow velocity in patients with PCCI, indicating that hypoperfusion is an important factor leading to an infarction in the posterior circulation [21]. TCD is a non-invasive measure of intracranial CBF velocity, which is usually associated with changes in blood ow [22].…”
Section: Discussionmentioning
confidence: 99%
“…The researchers believe that this is due to compensation by the contralateral vertebral artery to ensure normal cerebral perfusion. [19] Our study compared the effect of two different treatment methods on the hemodynamics of the vertebral-basal artery. The results showed that the PSV, EDV in the stenotic vertebral artery and PSV in the basilar artery were significant higher in the stenting group than in the drug treatment group.…”
Section: Discussionmentioning
confidence: 99%